The Relationship of the Quality of Nursing Services With the Level of Satisfaction of Inpatient Patients - Era Zana Nisa; Balqis Nurmauli Damanik; Christo Christo (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
The quality of nursing services is the appearance/performance that refers to the level of perfection of nursing services which on the one hand can give rise to satisfaction for each patient in accordance with the average level of satisfaction of the population and on the other hand and the procedures for administering it in accordance with the standards of the professional code of ethics that have been established, while satisfaction The patient is a level of feeling that arises as a result of the performance of the nursing service he received after the patient compared it with what he expected. So the quality of nursing services received by patients will influence the level of patient satisfaction. The aim of this research is to determine the relationship between the quality of nursing services and the level of satisfaction of inpatients at RSU. Perbaungan Jasmine, Serdang Bedagai Regency. The research design used was an analytical survey with a cross sectional approach. The number of samples found was 72 respondents. Data collection was carried out using quota sampling technique. Data were analyzed using chi square with a significance level of p<0.05. The results of the research show that there is a relationship between the quality of nursing services and the level of satisfaction of inpatients at RSU. Perbaungan jasmine, Serdang Bedagai Regency with a p-Value of 0.000. Based on this research, it was concluded that the higher the value of the quality of nursing services, the higher the level of patient satisfaction felt and conversely, the lower the quality of nursing services, the lower the level of patient satisfaction felt.